Impact of COVID-19 on mode choice behavior: A case study for Dhaka, Bangladesh. (September 2022) - Paul, Tonmoy; Chakraborty, Rohit; Afia Ratri, Salma; Debnath, Mithun
Highlights: Focused on the changes in mode choice behavior of Dhaka people due to COVID-19 pandemic while they are on the road. Multinomial Logit (MNL) model based on a utility function has been used to investigate the significance of the socio-demographic attributes and travel characteristics of the trips on the mode choice behavior. Inertia analysis using Sankey diagrams show that the mode choices to a large extent has been shifted to non-motorized vehicles (NMVs) from all other categories for both commute and discretionary trips during the pandemic. Temporal comparison of trip characteristics perspective using stacked graphs show that public transports are the least reliable modes during the pandemic and NMVs are the most cost-effective modes in commute trips. Suggested some viable policy making implications to cope with the current pandemic and relatable future national and global crises. Abstract: To ensure safety against the COVID-19, along with all other countries, Bangladesh as a least-developed country needs to deal with the changes in travel behavior, particularly changes in mode choice behavior. As Dhaka has been marked as a hotspot for the virus contagion, this paper has focused on the changes in mode choice behavior of Dhaka people due to the COVID-19 pandemic while they are on the road. A web-based questionnaire survey was conducted to capture the information on mode preferences and perspectives on travel characteristics for commute and discretionary trips before and during COVID-19. Multinomial Logit (MNL) model based on a utility function has been used to investigate the significance of the socio-demographic attributes and travel characteristics of the trips on the mode choice behavior and to calculate the maximum utility of the mode choice. This study highlighted some noticeable changes in perspective towards mode choice. People prefer walking, private cars, and rickshaw more during the pandemic as they feel these modes are more reliable, available, and cost-effective in this crucial time. Usage of public transportation dropped drastically for discretionary purposes. Additionally, usage of the on-demand vehicle increased during the pandemic as a large portion of commuters shifted to on-demand vehicles from public transportation. Furthermore, this paper suggested some viable policy-making implications to cope with the current pandemic and relatable future national and global crises. Finally, the paper concludes by suggesting some future research insights.